Note on the paleobiogeography of Compsognathidae (Dinosauria: Theropoda) and its paleoecological implications - SALES,MARCOS A.F. (2014)
The paleobiogeography of the theropod clade Compsognathidae is here reaccessed in order to test the hypothesis of this taxon being adapted specifically to inhabit semi-arid environments. Data about localities where these fossils were collected and their paleoenvironments were gathered from the literature. Compsognathids seem to be found especially in sedimentary deposits known as Fossil Lagerstätten, which were formed under a set of specific conditions that allowed the preservation of the fragile bone remains of these animals. This bias limits an accurate analysis of the historical and/or ecological paleobiogeography of this taxon. Actually, it is possible that compsognathids had an almost worldwide distribution during the Mesozoic Era. Their occurrence in Lower Cretaceous rocks of China suggests that they also inhabited environments with moist conditions instead of being restricted to semi-arid to arid environments.